2018
DOI: 10.1091/mbc.e17-01-0057
|View full text |Cite
|
Sign up to set email alerts
|

Stu2 uses a 15-nm parallel coiled coil for kinetochore localization and concomitant regulation of the mitotic spindle

Abstract: The yeast microtubule polymerase Stu2’s C-terminal domain is a 15-nm parallel, homodimeric coiled coil with two spatially distinct conserved regions. Determinants in these conserved regions optimally position Stu2 on the mitotic spindle to drive proper spindle structure and dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…How so many proteins compete for a small region of Stu2 raises interesting questions about cellular regulation that will need to be resolved in future studies. We also found that Stu2's coiled-coil domain is also required for its kinetochore association, consistent with recent work in cells (Haase et al, 2018;Humphrey et al, 2018).…”
Section: Stu2 Utilizes Multiple Domains To Achieve Kinetochore Associsupporting
confidence: 91%
See 2 more Smart Citations
“…How so many proteins compete for a small region of Stu2 raises interesting questions about cellular regulation that will need to be resolved in future studies. We also found that Stu2's coiled-coil domain is also required for its kinetochore association, consistent with recent work in cells (Haase et al, 2018;Humphrey et al, 2018).…”
Section: Stu2 Utilizes Multiple Domains To Achieve Kinetochore Associsupporting
confidence: 91%
“…We identified two domains in Stu2 required for its kinetochore association, the extreme Cterminus and the coiled-coil domain, consistent with prior work (Haase et al, 2018;Humphrey et al, 2018). We propose that Stu2's C-terminal tail domain (residues 855-888) directly interacts with Ndc80c, and that two copies of Stu2's C-terminal domain are required to "sandwich" its binding motif on Ndc80c.…”
Section: Stu2 Utilizes Multiple Domains To Achieve Kinetochore Associsupporting
confidence: 86%
See 1 more Smart Citation
“…This domain coincides with the domain responsible for Stu2p dimerization (Wolyniak et al, ). This domain of Stu2p also is required for its recruitment to the kinetochore and SPB (Haase et al, ). As SUMO is known to regulate the dimerization of several of its targets (Bossis et al, ; Rojas‐Fernandez et al, ), we are currently working to determine whether SUMO regulates the dimerization of Stu2p.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in microtubule polymerization and nucleation, it is responsible for microtubule anchorage at MTOCs (Podolski et al, ; Usui, Maekawa, Pereira, & Schiebel, ; Wang & Huffaker, ). Stu2p also functions at the kinetochore, helping to attach MTs to the outer kinetochore plaque (Haase et al, ; Miller et al, ; Pearson, Maddox, Zarzar, Salmon, & Bloom, ; Suzuki et al, ). The kinetochore contains several sumoylated proteins, including its sumoylated partner, Ndc80p (Aravamudhan et al, ; Montpetit et al, ).…”
Section: Discussionmentioning
confidence: 99%